Factors governing the formation, distribution and taxonomy of soils with glossic horizons and features in the contiguous USA - Bockheim, James G.; Hodges, Ryan C.; Hartemink, Alfred E. (Geoderma Regional, 2025)
Soils with glossic horizons and features (referred to here as glossic soils) have horizons with interfingering of albic materials in the upper part of an underlying argillic or natric horizon. In the contiguous (exclusive of Alaska and Hawaii and US territories) USA there are 739 soil series covering 227,000 km2 with a glossic horizon or glossic features. Here we analyze site factors and soil properties that govern their formation, distribution and taxonomic classification. Seven distinctive geographic regions containing glossic soils were examined: the Great Lakes (37 % of area), Gulf Slope (23 %), Lower Mississippi Valley (12 %), Central Thin Loess-Till region (9 %), Rocky Mountains (9 %), Northern Great Plains (6 %), and Florida Flatwoods (2 %). Glossic soils in these regions have the following features: 90 % of the soil series are well, moderately well, or somewhat poorly drained, 92 % are covered with broadleaved or mixed broadleaved-coniferous forest, 92 % are deep or very deep (>100 cm), 85 % have mixed or siliceous mineralogy according to Soil Taxonomy (ST), 73 % have a coarse-loamy, fine-loamy, fine-silty, or fine particle size class according to ST, and 70 % of the soils have a base saturation > 70 % in the 0 to 50 cm depth. About 40 % of what was once may have been the argillic or natric horizon has been degraded, but some argillic horizons in the Great Lakes and Lower Mississippi Valley have been completely degraded to depths of >200 cm. Five constructs explaining the origin of glossic horizons are explored, including (i) lithologic discontinuities, (ii) a former periglacial climate and permafrost, (iii) shifts in ecotones related to climate change, (iv) increased podzolization following leaching of carbonates; and (v) redox processes derived from a fluctuating water table. Glossic soils occur on sediments dated from early Holocene to early Pleistocene age, or older. About 38 % of the soil series likely have never experienced permafrost or a periglacial climate. Formation of a glossic horizon or features is a retrograde form of pedogenesis initiated by the loss of carbonates, acidification, and the development of redoximorphic features. This process may be driven by natural stages in pedogenesis or by major changes in early Holocene climate and vegetation. About two-thirds of the glossic soils in the contiguous USA do not meet the requirements of albeluvic glossae or retic properties in the WRB classification system. •Glossic soils have albic materials in the underlying argillic or natric horizon.•We analyzed site factors and soil properties that govern their formation, distribution and classification.•Glossic soils occur on sediments dated from early Holocene to early Pleistocene age, or older.•Glossic horizons are initiated by the loss of carbonates, acidification, and the development of redoximorphic features.